2021
DOI: 10.2174/1874842202108010001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Phthalates and Terephthalates from Plant Material – Natural Products or Contaminants?

Abstract: Dialkyl phthalates have been used as plasticizers in polymers for decades. As mobile, small weight molecules, phthalates have entered the environment, where they have become ubiquitous. On the other hand, phthalates continue to be isolated from natural sources, plants, bacteria and fungi as bona fide natural products. Here, doubt remains as to whether the phthalates represent actual natural products or whether they should all be seen as contaminants of anthropogenic origin. The following article will review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 185 publications
0
7
0
Order By: Relevance
“…Phthalates was detected as one of the components from the GCMS analysis of the P31 extracts however phthalates are mostly used as plasticizers in polymer industry. The natural origin of phthalates are also reported having antimicrobial and other pharmacological properties isolated from fungi, plants, and algae [59,60,66]. Out of six different compounds present in band E, the nature of 2,4-di-tert-butylphenol was also reported as an anti-MRSA compound [58].…”
Section: Discussionmentioning
confidence: 99%
“…Phthalates was detected as one of the components from the GCMS analysis of the P31 extracts however phthalates are mostly used as plasticizers in polymer industry. The natural origin of phthalates are also reported having antimicrobial and other pharmacological properties isolated from fungi, plants, and algae [59,60,66]. Out of six different compounds present in band E, the nature of 2,4-di-tert-butylphenol was also reported as an anti-MRSA compound [58].…”
Section: Discussionmentioning
confidence: 99%
“…As additional substances that were detected in extract A, phthalates (naphthalene and phthalic acid) were related to contamination from plastic bags which contained insect samples until the analyses. It was reported that this type of compounds can be released from plastic containers (Venditti 2020), and they were observed in various ethanolic extracts of plants (Thiemann 2021) due to ethanol could probably be contained in plastic bottles. However, in this study, all the used solvents were stored in glass bottles.…”
Section: A3 Biological Activities Reported For Compounds Detected In ...mentioning
confidence: 95%
“…Most of the research related to these two processes has been conducted on microalgae. Microalgae show promise as bioremediation options for EAS in treatment plants [14] and important sources of phthalate biosynthesis [3,46].…”
Section: Rhodymenia Corrallina 5 a (W) A (W)mentioning
confidence: 99%